Observations of the Polar Ionosphere by the Vertical Incidence Pulsed Ionospheric Radar at Jang Bogo Station, Antarctica - Young-Bae Ham; Geonhwa Jee; Changsup Lee; Hyuk-Jin Kwon; Jeong-Han Kim; Nikolay Zabotin; Terence Bullett (Journal of Astronomy and Space Sciences, 2020)
Korea Polar Research Institute (KOPRI) installed an ionospheric sounding radar system called Vertical Incidence Pulsed Ionospheric Radar (VIPIR) at Jang Bogo Station (JBS) in 2015 in order to routinely monitor the state of the ionosphere in the auroral oval and polar cap regions. Since 2017, after two-year test operation, it has been continuously operated to produce various ionospheric parameters. In this article, we will introduce the characteristics of the JBS-VIPIR observations and possible applications of the data for the study on the polar ionosphere. The JBS-VIPIR utilizes a log periodic transmit antenna that transmits 0.5–25 MHz radio waves, and a receiving array of 8 dipole antennas. It is operated in the Dynasonde B-mode pulse scheme and utilizes the 3-D inversion program, called NeXtYZ, for the data acquisition and processing, instead of the conventional 1-D inversion procedure as used in the most of digisonde observations. The JBS-VIPIR outputs include the height profiles of the electron density, ionospheric tilts, and ion drifts with a 2-minute temporal resolution in the bottomside ionosphere. With these observations, possible research applications will be briefly described in combination with other observations for the aurora, the neutral atmosphere and the magnetosphere simultaneously conducted at JBS.